THE EFFECT OF ARTIFICIAL INTELLIGENCE, WORK-LIFE BALANCE, DIGITAL LEADERSHIP, AND JOB SATISFACTION ON EMPLOYEE ENGAGEMENT AND EMPLOYEE PERFORMANCE IN THE HYBRID WORK ERA AT PT XYZ - Sadiqin, Amin; Hwihanus, Hwihanus (Penerbit Lafadz Jaya, 2025)
The development and changes in work patterns due to the digital era have encouraged organizations to adapt to hybrid work systems that demand high flexibility and efficiency. This study aims to analyze the influence of Artificial Intelligence, Work-Life Balance, Digital Leadership, and Job Satisfaction on Employee Engagement and Employee Performance in the hybrid work era at PT XYZ. In addition, this study also examines the role of Employee Engagement as a mediating variable in the relationship between these variables, using a quantitative approach with the Partial Least Squares - Structural Equation Modeling (PLS-SEM) method processed through SmartPLS 4.0 software. The study population was all PT XYZ employees who work with a hybrid system, with a sample size that meets the criteria determined by the purposive sampling technique. The research instrument was a questionnaire (Likert scale 1–5). The results show that Artificial Intelligence, Work-Life Balance, Digital Leadership, and Job Satisfaction have a positive and significant effect on Employee Engagement. In addition, Artificial Intelligence, Digital Leadership, Job Satisfaction, and Employee Engagement also have a significant effect on Employee Performance, while the direct effect of Work-Life Balance on Performance is insignificant. This finding proves that Employee Engagement plays a role as an important mediating variable that bridges the influence of organizational factors on employee performance. The implications of this study indicate that companies need to strengthen the implementation of AI-based technology, build an adaptive digital leadership style, maintain work-life balance, and increase job satisfaction in order to create emotionally engaged employees who have optimal performance in the hybrid work era.